From Conceptual to Logical Schema: An LLM-based Approach - Silva, Hudson Afonso Batista da; Santos, Vitória Soares dos; Dorneles, Carina Friedrich; Mello, Ronaldo dos Santos (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS), 2025)
The use of language models for solving computational tasks has grown in recent years. Generating logical models from conceptual modeling (ER) is a specialized task with well-defined rules, performed by database specialists. This paper presents an experimental investigation into the capabilities of large language models (LLMs), including GPT, Gemini, and Claude, in generating logical models from conceptual representations. The results demonstrate that the Claude model exhibits superior results in addressing the proposed task.